calculus

differentiate the following funcation:

R(t) = (t + e^t)(4- sqrt (t))




asked by Zoe
  1. http://www.jiskha.com/display.cgi?id=1309066703

    posted by drwls

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math:)

    A person is on the outer edge of a carousel with a radius of 20 feet that is rotating counterclockwise around a point that is centered at the origin. What is the exact value of the position of the rider after the carousel rotates
  2. trigo help!

    1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. differentiate 3/{sin(3x+pi)} 4. differentiate pxsin(q/x)where p and q are constants. 5. differentiate xsin(a/x) where a is constant 6. differentiate sec^3(3x^2+1)
  3. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine
  4. Calculus

    Differentiate the given function. f(t)= 4(sqrt(t^3)) + 14/sqrt(t) - sqrt(17) f'(t)=?
  5. Calculus

    Could someone please explain this to me? Differentiate. h(u)= 10^(sqrt(u)) h'(u)= 10^(sqrt(u))*log(10)(d/du(sqrt(u))) h'(u)= 10^(sqrt(u))*((1)/(2*sqrt(u)))*log(10)
  6. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which
  7. MATH

    hi i was just wondering if u could help me with this math problem. find dy/dx at the indicated point in two different ways (a)solve for y as a function of x and differentiate (b) differentiate implicity. 1. y^2=3x+1 (5, -4) how do
  8. Calc.

    Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x)
  9. calculus

    Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln y = x ln(cos x) (dy/dx)/(y)= ln(cos x) (dy/dx)= y ln(cos x) = (cos x)^x * (ln cos x) (dx/du)= x(cos x)^(x-1) * (-sin x) = - x sin(x)cos^(x-1)(x)
  10. Calculus

    Differentiate the function. g(u) = sqrt(2)u+sqrt(7u) g'(u)=?

More Similar Questions